2013
DOI: 10.1016/j.bbadis.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 enhances bile-duct proliferation and fibrosis in Abcb4−/− mice

Abstract: Adamant progression of chronic cholangiopathies towards cirrhosis and limited therapeutic options leave a liver transplantation the only effective treatment. Insulin-like growth factor 1 (IGF1) effectively blocks fibrosis in acute models of liver damage in mice, and a phase I clinical trial suggested an improved liver function. IGF1 targets the biliary epithelium, but its potential benefit in chronic cholangiopathies has not been studied. To investigate the possible therapeutic effect of increased IGF1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…Interestingly, the reduction of hepatic IGF-1 expression was correlated directly with hepatocellular damage (AST, ALT) and with cholestatic indices (ggt and bilirubin). These findings underlined the importance of IGF-1 as protective factor against the deleterious effect of TNF, IL1-and cholestasis that lead to hepatocyte necrosis and fibrosis [16,17,25,32]. We also found a direct correlation between the hepatic expression of IGF-1 and the weight of the patients; this finding and the reduction of albumin in advanced stage of fibrosis confirm the role of the liver as the primary IGF-1 manufacturer with systemic anabolic effects [33].…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, the reduction of hepatic IGF-1 expression was correlated directly with hepatocellular damage (AST, ALT) and with cholestatic indices (ggt and bilirubin). These findings underlined the importance of IGF-1 as protective factor against the deleterious effect of TNF, IL1-and cholestasis that lead to hepatocyte necrosis and fibrosis [16,17,25,32]. We also found a direct correlation between the hepatic expression of IGF-1 and the weight of the patients; this finding and the reduction of albumin in advanced stage of fibrosis confirm the role of the liver as the primary IGF-1 manufacturer with systemic anabolic effects [33].…”
Section: Discussionsupporting
confidence: 75%
“…[44][45][46] In this study, real-time RT-PCR showed that the expression of CK-19 was detected at a low level in normal mouse liver (Control) and significantly increased on day 30 after CCl 4 injection (Fig. 4B), suggesting that increased bile duct epithelial cells may be a marker of CCl 4 -induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, correlative data supports a role for TIMP2 in protecting the ECM from proteolysis in fracture healing [30], keloids [31], liver [32,33], kidneys [34,35], Dupuytren's contracture [36,37], and in heart tissues [38][39][40][41][42]. As a specific example, patients suffering from Dupuytren's contracture, a disease caused by excessive ECM deposition leading to fixed flexion of joints in the hand, have a disruption in the balance between TIMP2 and MMP2 in favor of TIMP2, which suggests that increased TIMP2 is associated with pathophysiological ECM accumulation [36,37].…”
Section: Timp2 Direct Inhibition Of Ecm Proteolysis By Timp2mentioning
confidence: 93%